Perio-ortho interdisciplinary approach in a 50-year-old patient: A case report with 5-year follow-up - Swati Agarwal (Wolters Kluwer Medknow Publications, 2021)
Esthetic demands for correction of irregularities of dentition are becoming a prime concern even in patients above the age of 40 years. Severe periodontitis, being insidious, if present simultaneously, complicates the situation. Periodontally compromised adult patients requiring the treatment for malaligned teeth are encountered very frequently in daily practice, and the correction of these requires a combined perio-ortho interdisciplinary approach. The present case report deals with a 5-year follow-up of a case whose prime concern was rotated anterior teeth in the maxillary arch. However, along with this, severe periodontitis was also present. Open flap debridement along with osseous grafting was done wherever required, followed by fixed adjunctive orthodontic treatment. After the completion of orthodontic treatment, a fixed retainer in the form of splinting was given and the entire treatment met the esthetic along with functional demands of the patient. Early 6 months followed by yearly follow-ups reflected clinical and radiographic improvements in the dentition.